Future frontiers in paediatric oncology (UCC Student Medical Journal, 2024)
Paediatric oncology is the field of medicine relating to the care and treatment of childhood cancers. Over the past two decades, the remission rate has been increasing due to improved treatment methods; however, a number of aggressive forms of malignancy still affect this cohort. These rarer forms of cancer do not respond well to conventional treatment, presenting a significant challenge for paediatric oncologists due to their unique genetic profile and rapid progression. This paper seeks to explore two new frontiers in paediatric cancer treatment: the fields of genetic testing and targeted treatment strategies. Combined, both of these domains not only present a promising approach toward treating childhood cancers through personalised medicine, but also earlier detection leading to improved survival rates
Keywords: Oncology; Paediatric Oncology; Genetics; CRISPR